ANALISIS PENGUKURAN TINGKAT KAPABILITAS TERHADAP WEBSITE PONDOK PESANTREN ASSHIDDIQIYAH 2 TANGERANG DENGAN MENGGUNAKAN FRAMEWORK COBIT 5.0 PADA DOMAIN DELIVER, SERVICE & SUPPORT (DSS) DAN MONITOR, EVALUATE & ASSESS (MEA) - Taufik Ismail Asra (2023)
The development of science and technology in Indonesia has progressed very rapidly. The progress that is most felt by people's lives today, one of which is progress in the field of Information and Communication Technology. Science and technology in general have a close relationship, especially in the field of Islamic education, one of which is Islamic boarding schools. Islamic boarding schools are Islamic-based educational institutions that are developed Indigenously by the community. The Asshiddiqiyah 2 Tangerang Islamic Boarding School website has many shortcomings, these deficiencies are website constraints. The website is still semi-online, there is a need for feature updates such as full-online registration of new students. The purpose of this study is to determine the measurement of the level of capability of the Asshiddiqiyah 2 Tangerang Islamic boarding school website with the COBIT 5.0 framework, especially in the field of Islamic schools with aspects of the DSS and MEA domains. This research method is a quantitative method by distributing questionnaires to approximately 94 user respondents as well as Capability Level and GAP Analysis values from the COBIT 5.0 framework. The results of this study indicate that the validity test with a significance level of 0.202 and the reliability test with a Cronbach's Alpha value of 0.905 are declared valid and reliable data respectively. Then, the average Capability Level results in the DSS01, DSS03, DSS05, MEA01 and MEA02 subdomains were 1.4. This level is at level 1 (Performed Process) of the target level to be achieved on the IT side of the Pondok Pesantren Asshiddiqiyah 2 Tangerang website which is level 4 (Predictable Process).